Limitaciones que tienen los tenderos del municipio de Belén - Boyacá al momento de hacer parte del sistema financiero. (2020)
In Colombia, the banking process has been increasing, reaching 83.3% of the population in September 2019, that is, approximately 29 million inhabitants. This process has been greatly stimulated by the articulated work of different public and private entities. Other external factors, among which the COVID-19 pandemic stands out, have motivated a greater opening of financial products with a view to receiving government aid and other economic benefits. In this order of ideas, it is pertinent to identify the conditions and limitations of access to the financial system of the shopkeepers of the municipality of Belén Boyacá, having as a premise that this sector represents one of the main economic activities of the municipality.